Learning from the Design and Implementation of Large-Scale Programs to Improve Infant and Young Child Feeding. Issue 3 (September 2013) - Baker, Jean; Sanghvi, Tina; Hajeebhoy, Nemat; Abrha, Teweldebrhan Hailu
Background: Improving and sustaining infant and young child feeding (IYCF) practices requires multiple interventions reaching diverse target groups over a sustained period of time. These interventions, together with improved maternal nutrition, are the cornerstones for realizing a lifetime of benefits from investing in nutrition during the 1000 day period. Objective: Summarize major lessons from Alive & Thrive's work to improve IYCF in three diverse settings—Bangladesh, Ethiopia, and Vietnam. Methods: Draw lessons from reports, studies, surveys, routine monitoring, and discussions on the drivers of successful design and implementation of IYCF strategies. Results: Teaming up with carefully selected implementing partners with strong commitment is a critical first step. As programs move to implementation at scale, strategic systems strengthening is needed to avoid operational bottlenecks. Performance of adequate IYCF counseling takes more than training; it requires rational task allocation, substantial follow up, and recognition of frontline workers. Investing in community demand for IYCF services should be prioritized, specifically through social mobilization and relevant media for multiple audiences. Design of behavior change communication and its implementation must be flexible and responsive to shifts in society's use of media and other social changes. Private sector creative agencies and media companies are well equipped to market IYCF. Scaling up core IYCF interventions and maintaining quality are facilitated by national-level coordinating and information exchange mechanisms using evidence on quality and coverage. Conclusions: It is possible to deliver quality IYCF interventions at scale, while creating new knowledge, tools, and approaches that can be adapted by others and contribute to accelerated scale up of IYCF programs globally.